Sustainable Use of Recycled Asphalt Pavement in Soil Stabilization - Danilo Lima; Jair Arrieta-Baldovino; Ronaldo L. S. Izzo (Civil Engineering Journal, 2023)
This study addresses unused recycled asphalt pavement (RAP) incorporated into sedimentary soil from the Guabirotuba Formation in Curitiba, Southern Brazil. Different percentages of RAP, ranging from 0% to 80% by weight, were mixed with the pure soil, with and without the addition of pozzolanic Portland cement. Tests were conducted to evaluate the mixtures' compaction properties, mechanical strength, and expansion after curing for up to 28 days. The results showed that adding RAP improved the mixtures' unconfined compressive strength (qu) and splitting tensile strength (qt). Up to 60% RAP, the qu increased by 260 kPa, and the qt increased by 340 kPa compared to the pure soil. The California Bearing Ratio (CBR) tests demonstrated an 18.62% improvement when 80% RAP was added to the untreated soil. In addition, the RAP also reduced the expansion of the compacted blends, with values decreasing from 1.19% to 0.88% with 80% RAP replacement. The expansion value was further reduced to 0.86% when the cement was added. The cement-soil-RAP compacted blends showed suitability for subgrade reinforcement, meeting the criteria of expansion <1% and CBR> 2%. Additionally, 3% cement and 40% RAP mixtures were suitable as a sub-base layer, with expansion <1% and CBR > 20%. The results provide valuable insights into utilizing RAP as an alternative material in soil improvement techniques employing the novelty porosity-to-cement index.Â Doi: 10.28991/CEJ-2023-09-09-016 Full Text: PDF